INDUSTRIAL STRUCTURE AND SPATIAL DISTRIBUTION OF INDUSTRY IN DAGESTAN IN THE PERIOD OF THE GREAT PATRIOTIC WAR OF 1941-1945 - Mirzabekov, M A (History, Archeology and Ethnography of the Caucasus, 2015)
Basing on the a wide range of various sources, the author of the article demonstrates the work of bodies of government and labor collectives of the republic on restructuring industry to production of military goods, changes in the industrial composition and territorial distribution of branches of industry in the multinational region and the assortment of products. The author mentions the role of industrial enterprises and personnel evacuated from other regions of the country in the increase of production of arms, ammunition and other products required for the front. The article presents the efforts of particular industries and enterprises to realize production objectives, the difficulties associated with the lack of raw materials, which reflected adversely on the rhythm of work of enterprises and branches of industry and on the implementation of plans of manufacturing. The author highlights the role of regional and local industry in meeting the consumer demand of the population of Dagestan.